A target-driven DNA-based molecular machine for rapid and homogeneous detection of arginine-vasopressin. Issue 3 (11th December 2019) - Tan, Haocheng; Chen, Lu; Li, Xinyi; Li, Mengyuan; Zhao, Meiping
Abstract : A DNA-based molecular machine triggered only by a specific target neuropeptide has been developed and integrated with fluorescence signal amplification system. It enabled rapid and sensitive detection of the target neuropeptide in biological matrices. Abstract : Rapid detection of physiological changes of neuropeptides is of great importance as they are involved in a wide range of physiological processes and behaviors. Abnormalities in their expression level are correlated with various neurological diseases. However, current methods such as radioimmunoassay, enzyme-linked immunosorbent assays and liquid chromatography tandem mass spectrometry relied on cumbersome operation steps and could not rapidly provide the information of their concentration fluctuations. Thus motivated, we developed a target-driven DNA-based molecular machine that could be triggered only in the presence of a specific target neuropeptide. Using arginine-vasopressin (AVP) as a model neuropeptide, we integrated the DNA-based molecular machine with fluorescence signal transduction and amplification technology. The assay was rapid and homogeneous, which offered a linear range of 75–700 pM and a limit-of-detection as low as 75 pM. It holds great potential for further applications in real-time monitoring of the variations of the AVP level in biological samples.